Initial report of the genitourinary and gastrointestinal toxicity of post-prostatectomy proton therapy for prostate cancer patients undergoing adjuvant or salvage radiotherapy. (2nd November 2018) - Deville, Curtiland; Jain, Akansha; Hwang, Wei-Ting; Woodhouse, Kristina D.; Both, Stefan; Wang, Shiyu; Gabriel, Peter E.; Christodouleas, John P.; Bekelman, Justin; Tochner, Zelig; Vapiwala, Neha
Abstract: Purpose: To report acute and late genitourinary (GU) and gastrointestinal (GI) toxicities associated with post-prostatectomy proton therapy (PT). Methods: The first 100 consecutive patients from 2010 to 2016 were retrospectively assessed. Baseline characteristics, prospectively graded CTCAE v4.0 toxicities, and patient-reported outcomes were reported. Late outcomes were reported for 79 patients with 3 months minimum follow up. Toxicity-free survival Kaplan-Meier curves were estimated. Logistic regression assessed associations between toxicities and clinical and treatment characteristics ( p < .05 significance). Results: Median age, months after surgery, and months of follow-up were respectively 64 years (range 42–77), 25 (5–216), and 25 (0–47). PT received was 70.2 Gy (RBE) (89%), salvage (93%), prostate bed only (80%), pencil beam scanning (86%), with IMRT (31%), and with androgen deprivation (34%). Acute and late maximum toxicities, respectively were: GU grade 0 (14%; 18%), 1 (71%; 62%), 2 (15%; 20%), ≥3 (0), and GI: grade 0 (66%; 73%), 1 (34%; 27%), ≥2 (0). Toxicity-free survival at 24 months was GU grade 2 (83%) and GI grade 1 (74%). Mean (±std dev) baseline International Prostate Symptom Score (IPSS), International Index of Erectile Function, and Expanded Prostate Cancer Index Composite bowel function and bother were 6.6 ± 6.1, 10.5 ± 7.3, 90.9 ± 10.8, 93.3 ± 11.2, respectively, and largely unchanged at 2 years: 6.3 ± 3.6, 11.1 ± 6.3, 92.8 ± 5.8, and 90.9 ± 10.3. On multivariate analysis, baseline IPSS ( p = .009) associated with GU grade 2 acute toxicity. Bladderless-CTV median dose, V30, and V40 associated with GU grade 2 acute toxicity and maximum dose with late (Ps <0.05). For GI, on multivariate analysis, baseline bowel function ( p = .033) associated with acute grade 1 toxicity. Rectal minimum and median dose, V10, and V20, and anterior rectal wall median dose and V10 through V65 associated with acute grade 1 GI toxicity (Ps < .05). Conclusions: Post-prostatectomy PT for prostate cancer is feasible with a favorable GU and GI toxicity profile acutely and through early follow up.